Mechanical properties and mechanism of damage and deterioration of coal under cyclic loading - Ziwei Ding; Qingbao Tang; Xinwei Gong; Jindui Jia; Guangqing Di; Long Chen (Scientific Reports)
Abstract To analyze the mechanical characteristics of damaged coal bodies and the mechanisms of evolution and degradation of internal pore and fracture defects under cyclic loads, raw coal containing original pore and fracture materials was selected as the research material. This study investigates the impact of cyclic loading on the mechanical properties of damaged coal and the evolution of flaw structures, such as pores and cracks, within the coal. A micro-fracture size judgment index (C i ) was defined based on fracture volume to determine the dominant macroscopic failure mode in coal bodies. The results indicate that a “hysteresis loop” forms in the loading and unloading curves of each cycle due to cyclic loading. During the cyclic loading and unloading phase, both the loading elastic modulus and the damage parameters of coal samples increase proportionally with the level of loading and the number of cycles. In the constant amplitude cyclic loading and unloading phase, there is minimal variation in the loading elastic modulus and damage parameters of coal samples, indicating their stability. As micro-scale fractures evolve within the coal body, pores with a volume less than 109 μm3 decrease with increasing cyclic loading and unloading during amplification cycles but remain relatively stable during equal amplitude cyclic loading phases. The contribution rate of damage to fractures with a volume between 109 and 1011 μm3 increases with higher load levels and cyclic loading/unloading during both amplification and equal amplitude cycles. The minimum order of magnitude for fracture volume that dominates macroscopic failure in the coal body is determined to be 109 and 1010 μm3.